2011
DOI: 10.1017/s0016756811000872
|View full text |Cite
|
Sign up to set email alerts
|

Parental magma composition of the syntectonic Dawros Peridotite chromitites, NW Connemara, Ireland

Abstract: Chromium-spinels have been widely used as petrogenetic indicators to infer parent melt compositions and the tectonic setting of their formation. This study integrates petrographic, quantitative textural and geochemical analyses of Cr-spinel seams within the Dawros Peridotite, NW Connemara, Ireland to determine the composition of their parental magmas. Calculation of Cr no. (Cr/(Cr + Al)) (0.50-0.77) values and TiO 2 (0.18-0.36 wt %) contents of the Cr-spinel seams, coupled with an estimation of the Al 2 O 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…This new mechanism necessitates profound reassessment of existing petrogenetic models for chromitite deposits. We also infer that this mechanism can be extrapolated to explain the podiform chromitites that are commonly observed in ophiolites as well as non-ophiolitic peridotite complexes 34 36 . In addition, we predict that the origin of other magmatic deposits can ultimately be resolved by examining the consequences of lithostatic pressure reduction on liquidus phase equilibria.…”
Section: Discussionmentioning
confidence: 69%
“…This new mechanism necessitates profound reassessment of existing petrogenetic models for chromitite deposits. We also infer that this mechanism can be extrapolated to explain the podiform chromitites that are commonly observed in ophiolites as well as non-ophiolitic peridotite complexes 34 36 . In addition, we predict that the origin of other magmatic deposits can ultimately be resolved by examining the consequences of lithostatic pressure reduction on liquidus phase equilibria.…”
Section: Discussionmentioning
confidence: 69%
“…The Dawros site is situated near Letterfrack, Connemara, County Galway, western Ireland (53°34¢N; 9°58¢W). It is underlain by peridotite and the geology has been described by Rothstein (1957), Leake (1964) and Hunt et al (2012) among others. The vegetation is grazed grassland (Fig.…”
Section: Study Sitesmentioning
confidence: 99%
“…Bennett & Gibb (1983) alternatively suggested that it was possible the Dawros intrusion was emplaced as a separate body to the Currywongaun-Doughruagh gabbros. Hunt et al (2012) used mineral chemical and textural characteristics of Cr-spinel in chromitite layers from the Dawros intrusion to demonstrate that these rocks probably represent cumulates formed in an open-system, mid-to-lower crustal supra-subduction zone magma chamber.…”
Section: Geological Settingmentioning
confidence: 99%